2015
DOI: 10.5194/acpd-15-4495-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating global and North American methane emissions with high spatial resolution using GOSAT satellite data

Abstract: Abstract. We use 2009–2011 space-borne methane observations from the Greenhouse Gases Observing SATellite (GOSAT) to constrain global and North American inversions of methane emissions with 4° × 5° and up to 50 km × 50 km spatial resolution, respectively. The GOSAT data are first evaluated with atmospheric methane observations from surface networks (NOAA, TCCON) and aircraft (NOAA/DOE, HIPPO), using the GEOS-Chem chemical transport model as a platform to facilitate comparison of GOSAT with in situ data. This i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(106 citation statements)
references
References 62 publications
11
95
0
Order By: Relevance
“…This shows a mismatch between observations based and inventory based XCH4 anomalies over northern America and thereby a potential underestimation in the emission inventory. This result is in agreement with recent studies by Miller et al [12] and Turner et al [18] who showed anthropogenic CH4 emission in North America is underestimated by 30-50%, attributable to oil and natural gas and livestock emissions. Over the East Asian region, the model-observation mismatch is approximately 30%, emission being higher than suggested by observation derived enhancements.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This shows a mismatch between observations based and inventory based XCH4 anomalies over northern America and thereby a potential underestimation in the emission inventory. This result is in agreement with recent studies by Miller et al [12] and Turner et al [18] who showed anthropogenic CH4 emission in North America is underestimated by 30-50%, attributable to oil and natural gas and livestock emissions. Over the East Asian region, the model-observation mismatch is approximately 30%, emission being higher than suggested by observation derived enhancements.…”
Section: Resultssupporting
confidence: 83%
“…Similarly, differences between EPA and EDGAR in various emission sectors are discussed in Maasakkers et al [17]. Turner et al [18] applied a 50 km resolution inverse model utilizing GOSAT data over North America to conclude that EPA emission inventory is underestimating emissions by some sectors. Further, since the emission of methane from anthropogenic sources are highly variable within same source category, the quantification is much more difficult than anthropogenic emission of CO 2 which are deduced from better known fuel use data.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the polar region, the tropopause height varies strongly and the dynamical processes are complex. Turner et al (2015) compared GOSAT CH 4 with GEOS-Chem simulations, and found large differences at high latitudes. They proposed that the model bias in total column CH 4 at high latitudes comes from the stratosphere since the validation with TCCON (Total Carbon Column Observing Network), NOAA surface and aircraft measurements, and HIPPO shows good performances of the model in the troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…To properly exploit disparate data sources with differing spatio-temporal resolutions it will be useful to employ chemical models as intercomparison platforms. This methodology has been used previously to compare satellite measurements of ozone [124] and satellite measurements of methane and formaldehyde with in situ data [106,126].…”
Section: Validationmentioning
confidence: 99%